Effects of liquid smoke preparations on shelf life and growth of wild type mold and Aspergillus flavus in a model semi moist pet food - Deliephan, Aiswariya; Dhakal, Janak; Subramanyam, Bhadriraju; Aldrich, Charles G. (Frontiers in Microbiology, 2023)
Liquid smoke is a naturally derived flavor component and preservative with known antimicrobial properties. To our knowledge, there is a paucity of information on antifungal potential of liquid smoke against storage fungi like Aspergillus flavus that produce mycotoxins in human and pet foods. Semi-moist pet food with high moisture content (20-30%) is susceptible to mold contamination and requires intervention. The objectives of this study were to determine the effects of liquid smoke preparations on the growth of wild-type mold and A. flavus in semi-moist pet food. Semi-moist pet food was formulated with eight liquid smoke preparations at 0% (untreated), 0.5%, 1%, 2% and 4% (w/w). A positive control consisted of 0.2% potassium sorbate known to inhibit mold growth. Shelf life was estimated by storing the samples at 28°C and 65-70% RH over 30 days and recording number of days until the appearance of visible wild-type mold. In another experiment, samples were spot inoculated with A. flavus (~10,000 CFU/mL), incubated at 25°C, and analyzed for fungal growth by enumeration on potato dextrose agar, at sampling intervals of 2 days over a 35-day period. Liquid smoke at 0.5%, 1%, 2%, and 4% extended the shelf life of samples by 11.6, 12.5, 17.2, and 24.1 days when compared to the untreated samples (7.7 days). The smoke preparations Cloud S-C100 and Code-10 (high carbonyl, medium/low phenol) were the most effective in prolonging the number of days to visible mold growth (26-28 days). In the challenge study with A. flavus, Cloud S-C100, Cloud S-AC15 (high to medium carbonyl, low phenol), and Code 10 (base smoke) reduced mold counts by 1.0, 1.7, and 2.5 logs when compared to the untreated samples at 1, 2, and 4% respectively. Addition of smoke at 0.5% did not reduce mold counts. The carbonyl preparations of liquid smoke were the most effective at enhancing shelf life of semi-moist pet food, and at inhibiting A. flavus growth.